Model Hubungan Karakteristik Pemimpin dan Modal Sosial dalam Mempengaruhi Kinerja Lembaga Keuangan Mikro Syariah (LKMS) - Nurita Andriani; - Faidal (Trunojoyo University of Madura, 2014)
This study aims to determine the role of social capital in a growing community interaction ( as a customer ) with a managed LKMS on performance , which is to determine the ability of social capital in improving the performance LKMS activity that is based on the principles of : Siddiq , tabligh, amanah dan fatonah, determine the ability of social capital in improving the performance of the economic impact of the source of financing . This study also aims to determine the development efforts in the sphere of social capital LKMS -run boarding pesantren and how the influence of charisma kiai as a leader in the development of socialcapital. Social capital in this study include the capacity of members of the social capital that exist around schools by function , namely : cognitive aspects ( norms , trust, solidarity , and integrity ) and structural aspects ( network and groups ) . The output of these two aspects in the form of ideas or expectations that leads to collective behavior in order to generate collective profits . The one aspect that affects why the community is willing to do in order to produce the collective behavior collective profit anyway (mutually beneficial collective action,MBCA) and others serve to facilitate the MBCA, Research sites in Pamekasan , considering there are a number of boarding pondok pesantrenin Pamekasan who manage LKMS. By using purposive sampling to sampling techniques and research using SEM analysistools. Research results show that social capital is built in community interaction with Pondok Pesantren Darul Ulum Cooperatives play a role in improving the performance of LKMS . Growing social capital LKMS then increased performance , better performance of economic activity as well as its economic impact performance. Growth social capital impact to the increasing performance of institutions based on the principles shiddig , sermons , trustworthy , and fatonah ( performance of economic activity ) . Growth of social capital to the growing impact welfare and increasing the accessibility of financing sources ( economic impact performance ) . The impact of social capital influence on the performance of economic activity rather than on the performance of the economic impact.